Kinematic and neuromuscular responses to different visual focus conditions in stand-up paddleboarding - Freitas,João; Conceição,Ana; Stastny,Jan; Morais,Jorge E.; Marques,Diogo L.; Louro,Hugo; Marinnho,Daniel A.; Neiva,Henrique P. (PeerJ, 2025)
Purpose This study analyzed the kinematics and muscle activity during the stand-up paddleboarding (SUP) under different visual focus points in three conditions: i) eyes on the board nose, ii) looking at the turn buoy, and iii) free choice. Methods Fourteen male paddleboarders (24.2 ± 7.1 years) performed three trials covering 65 m, and the electromyographic (EMG) activation patterns and kinematic parameters in four cycle strokes for the left and right sides were analyzed. Surface EMG of the upper trapezius, biceps brachii, triceps brachii, tibialis anterior, and gastrocnemius medialis were recorded. The data were processed according to the percentage of maximum voluntary contraction (%MVC). Speed, stroke frequency (SF), stroke length, and stroke index (SI) were analyzed. Results The speed, SF, and SI (p < 0.01, η2 ≥ 0.42) showed significant variance between conditions, with the free condition achieving the highest speed (1.20 ± 0.21 m/s), SF (0.65 ± 0.13 Hz) and SI (2.25 ± 0.67 m2/s). This condition showed greater neuromuscular activity, particularly in the triceps brachii during both the left (42.25 ± 18.76 %MVC) and right recoveries (32.93 ± 16.06 %MVC). During the pull phase, the free choice presented higher biceps brachii activity (8.51 ± 2.80 %MVC) compared to the eyes on the board nose (6.22 ± 2.41 %MVC; p < 0.01), while showing lower activity in the triceps brachii (10.02 ± 4.50 %MVC vs. 16.52 ± 8.45 %MVC; p < 0.01) and tibialis anterior (12.24 ± 7.70 %MVC vs. 17.09 ± 7.73 %MVC; p < 0.01) compared to looking at the turn buoy. Conclusion These results suggest that a free visual focus allows paddleboarders to enhance their kinematics and muscle activation, highlighting the significance of visual focus strategies in improving both competitive and recreational SUP performance.
Keywords: Muscle activation; EMG; Recreational-level; Stroke length; Stroke frequency; Stand-up paddle